Modelos e intervenções de cuidado transicional após o acidente vascular cerebral: scoping review - Mendonça, Lívia Machado (2017)
People who experience stroke face limitations and assistance weaknesses, especially with regard to the continuity of care at different levels of health care, which can generate fragmented assistance and less than the ideal recommended to ensure safety and quality of the health care. In addition, in view of the high risk for recurrence of cerebrovascular events and high readmission rates, it has been increasingly recommended to adopt protocols for the promotion of transitional care. Therefore, the purpose of this scoping review was to map the models and interventions of this type of care in cases of stroke. Methodological assumptions of Arksey and O'Malley were adopted, with the recommendations of Levac, Colquhoun and O'Brien. A search was carried out in databases MEDLINE, CINAHL, PsychINFO, SCOPUS and EMBASE, and the gray literature was accessed at Google scholar, Joint Commission International, National transitions of Care Coalition and Agency for Healthcare Research and Quality.The data were summarized in terms of the general characteristics of the publications and the narrative synthesis referring to the models and the transitional care interventions specific for stroke cases. Of the 32 studies included, most were published in the United States (8 articles), Canada (5 articles) and the United Kingdom (4 articles), in specific thematic journals for rehabilitation (16 articles). Regarding methodological approaches, experimental studies (14 articles), mixed methods (3 articles), qualitative studies (4 articles), observational (2 articles), surveys (2 articles), systematic reviews with meta-analysis (2 articles), conceptual reviews (2 articles) and a guideline were identified. Nine studies have addressed transitional care models and 23 transitional care interventions related to stroke. Explanatory models on the experience of patients and caregivers in the care trajectory and descriptive models of recommendations for the design of transitional care interventions were identified. It was verified that the majority of the interventions used pre and post-discharge components of the Ideal Transition of Care model, especially patient education for self-management, monitoring and symptom management after discharge and discharge planning. The most used model was Early Support Discharge. The studies analyzed identified favorable results after the implementation of transitional care interventions and demonstrated that this is a thematic area for which efforts should be made to subsidize resources to improve the quality of care transition management